Respostas
respondido por:
1
z=(1+i)/(1+i)
z=(1+i).(1-i)/(1+i).(1-i)
z=1-(-1)/1-(-1)
z=1+1/1+1
z=2/2
z=1
senϴ=b/|z|
senϴ=0/|1|
senϴ=0
cosϴ=a/|z|
cosϴ=1/|1|
cosϴ=1
Arg(z)=ϴ
ϴ=0°
espero ter ajudado!
bom dia !
z=(1+i).(1-i)/(1+i).(1-i)
z=1-(-1)/1-(-1)
z=1+1/1+1
z=2/2
z=1
senϴ=b/|z|
senϴ=0/|1|
senϴ=0
cosϴ=a/|z|
cosϴ=1/|1|
cosϴ=1
Arg(z)=ϴ
ϴ=0°
espero ter ajudado!
bom dia !
andreyvianacristo:
quase ajudou muito mano. mas esqueci de colocar ao quadrado z= ( 1+i ) ao quadrado 2 \ sobre 1 - i:
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás